Revised Code of Ordinances of the City of McKinney Page 16, Image 17 (1899) [Ordinances of the City of McKinney,] Ordinance No. 26 - (:unkn) unknown (My University, 1899)
§Be it ordained by the city council of the city of McKinney: § 1. That it shall be unlawful for any person to fire or shoot any gun, pistol, firecracker or any kind of fireworks or pyrotechnics in the corporate limits of the city of McKinney
Keywords: DISCHARGE